2012
DOI: 10.1182/blood-2011-08-373621
|View full text |Cite
|
Sign up to set email alerts
|

An acute negative bystander effect of γ-irradiated recipients on transplanted hematopoietic stem cells

Abstract: Ultimate success of hematopoietic stem cell transplantation (HSCT) depends not only on donor HSCs themselves but also on the host environment. Total body irradiation is a component in various host conditioning regimens for HSCT. It is known that ionizing radiation exerts "bystander effects" on nontargeted cells and that HSCs transplanted into irradiated recipients undergo proliferative exhaustion. However, whether irradiated recipients pose a proliferation-independent bystander effect on transplanted HSCs is u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
61
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(62 citation statements)
references
References 51 publications
1
61
0
Order By: Relevance
“…31 In addition, damage to the HSC niche, such as induction of BM stromal cell senescence, and a negative bystander effect of TBI on HSCs, also play a role in IR-induced residual BM injury. 32,33 Our studies also revealed that only a small fraction of HSCs became senescent at a time after TBI. This may be in part attributable to the immunosurveillance of senescent cells by immune cells that can rapidly remove senescent cells to prevent the accumulation of senescent cells in vivo.…”
Section: Discussionmentioning
confidence: 70%
“…31 In addition, damage to the HSC niche, such as induction of BM stromal cell senescence, and a negative bystander effect of TBI on HSCs, also play a role in IR-induced residual BM injury. 32,33 Our studies also revealed that only a small fraction of HSCs became senescent at a time after TBI. This may be in part attributable to the immunosurveillance of senescent cells by immune cells that can rapidly remove senescent cells to prevent the accumulation of senescent cells in vivo.…”
Section: Discussionmentioning
confidence: 70%
“…Previous studies, including those from our laboratory, indicated that acute BM radiation injury is, at least in part, attributable to the induction of apoptosis in HSPCs [3,6,18], suggesting that inhibition of IR-induced apoptosis may be an effective approach to protecting BM radiation injury. CAT is an extremely potent antioxidant We and others have demonstrated that IR-induced ROS play a critical role in radiation tissue injury [10][11][12][18][19][20]. IR induces ROS production in irradiated cells as a consequence of radiolysis of water, which can cause DNA damage, ultimately leading to apoptosis and/or cellular senescence.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that ectopic overexpression of CAT can protect a variety of tissues against oxidative stress-induced damage in animal models [19][20][21]. Furthermore, there is evidence indicating that CAT treatment may preserve hematopoietic stem cell (HSC) selfrenewal in long-term BM cultures [22].…”
mentioning
confidence: 99%
“…Consequently, it exerts a significant bystander effect on transplanted cells in marrow. 12 Thus, transplant protocols involving the use of TBI do not accurately reflect the conditions in leukemia patients. In addition, previous studies have focused on only one or a few HSC/HPC subsets, and they lacked data on the impact of leukemic hosts on the whole spectrum of different subsets of HSCs and HPCs in vivo.…”
Section: Introductionmentioning
confidence: 99%